Shear Waves Provide an Extra Control on Seismic Interpretation - Ali, Mubarik (Journal of Himalayan Earth Sciences, 1985)
Interpretation of shear wave arrivals in 40 km refraction line (LUST), by ray-tracing procedure, gives good correlation between Vs distribution and laterally varied lithology in the Precambrian Lewisian metamorphic complex of NW Britain. It provides an explanation for the Vp-spike detected in the uniform velocity environments of quartz-feldspathic gneisses of the northern belt, and Vp/Vs sheds more light on rapid velocity decrease in the retrogressed equivalents of pyroxene-granulites of the central belt. No evidence is found for shallow existence of pyroxene-granulites under the northern belt.